Exploring Mental Time Travel in Shakespeare’s Sonnets: A Neuropsychological Approach - Al-Abdullah, Mufeed (An Overview of Literature, Language and Education Research Vol. 7, 2024)
Time is a major subject in Shakespeare’s sequence of sonnets. Noticeably, the word “time” is mentioned seventy-nine times in the collection along with other relevant words like seasons, weeks, days, hours, and minutes. This study aims to analyze Shakespeare’s use of mental time travel (MTT) in his collection of sonnets, especially those addressed to his young friend. It also hopes to amplify that Shakespeare’s versification of MTT anticipates modern neuropsychological studies on the topic. The study isolates those sonnets that deal with issues relevant to MTT, such as time, life cycle, and memory. The issues are classed out into four different premises induced from the selected sonnets subject to analysis: first, MTT occurs in the sonnets in correlation with objective time; second, the dual constructive and destructive nature of time triggers the need for the memory-based MTT; third, the disparaging effect of time on the poet and the friend’s mother is meant to stimulate the young friend to heed the future of his extraordinary beauty under the strokes of ruthless time; and, fourth, the destructive force of time on non-human beings and natural phenomena provides another stimulus to urge the young friend to heed the dangers of time on his future. The study concluded that Shakespeare’s demonstration of the Aristotelian concept of chronological time places him within the traditions of the Renaissance which was informed and inspired by the massive movement of humanism. Yet Shakespeare is a poet of all times.